Dinamika nilai ekonomi interaksi masyarakat dengan CAPC Kota Jayapura - Yonas Nauw; Bambang Nugroho; Hendri (Program Pascasarjana Universitas Papua, 2023)
This study’s emphasis was on dynamics of economic value of people interaction at Cycloop Mountain Nature Reserve, Jayapura Municipality. A technical approach using documentation, observation, interviews, and supporting secondary data was completed through literature review. This research results showed that there are two main factors of people’s interaction. Firstly, land use change approximately 418 hectares as farm, settlement and hunting. In adition, the timber forest products as building material, firewood and charcoal was economics interest as a reason as livelihood that easy to people interac. Based on the total of economic value (TEV) analysis on utilasation of Cycllop’s ecosystems services was Rp.276,378,421,533,00 per year. The benefits of carbon credit (C-storage) is Rp. 272,778,407,829.00 per year; Indirect value of Cycloop’s forest services is Rp. 2,419,610,252.00 and direct value of Cycloop’s is Rp. 795,923,452.00 and which has the lowest value in the utilization of ecosystems and natural resources as direct benefit from comunity interaction is Rp. 384,480,000.00 per year. Secondly, the increase of population density as triggers of forest loss, due to limited availability of livelihood access and the community's understanding of the forest protected area. Besides that this is also an act against the law. However, it is necessary to conduct studies on law’s perspective on the role of Cycloops as well as to deal with forest degradation in local context. Moreover, it is also necessary to involve the people mindset on both forest role and forest law.